Menakar Peran Persepsi Harga dalam Penciptaan Keputusan Pembelian Jasa Wisata - Emaya Kurniawati; Aprih Santoso (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2023)
This research located in Mangkang Zoo. The aim of the research is to evaluate services that influence the decision to purchase tourism services at the Mangkang Zoo, Semarang, by considering perceptions of price as a moderating factor. This research shows that service quality has an impact on purchasing decisions at the Mangkang Zoo, Semarang. Meanwhile, other findings, namely price perception, show that service quality has an influence on purchasing decisions, with price as a mediating variable at the Mangkang Zoo, Semarang. This illustrates that management has succeeded in implementing an appropriate pricing policy, including in terms of price levels, special price offers, payment processes, payment terms, all of which are in line with the quality of the services provided. The population studied was visitors who decided to use tourist services at the Mangkang Zoo, Semarang, with an unspecified number. The sampling method was carried out by chance and involved 100 respondents. The research results are that service quality has an impact on the decision to purchase tourism services at the Mangkang Zoo, Semarang. Furthermore, perceptions of price also have a positive and significant influence in strengthening the correlation between service quality and purchasing decisions for tourism services at the Mangkang Zoo, Semarang.